Tinjauan Literatur: Integrasi Sinergis Media dan Model Pembelajaran IPA untuk Penguatan Keterampilan Abad ke-21 pada Siswa SMP - Amalia Kusuma Dewi; Ernita Vika Aulia; Muhamad Arif Mahdiannur (International Forum of Researchers and Lecturers, 2025)
The development of digital media and innovative learning models in Junior High School Science education reflects a sustained commitment to meeting the demands of 21st-century skills and improving the quality of science instruction. A comprehensive literature review (2019–2024) reveals the dominance of the Research and Development (R&D) approach, which consistently yields highly valid, practical, and effective digital resources, such as Augmented Reality (AR), Android-based applications, and interactive educational games. These digital tools are synergistically integrated with modern instructional models, including Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), and Predict-Observe-Explain (POE), which are proven effective in increasing student engagement, enhancing cognitive outcomes, and honing essential competencies such as Science Process Skills (SPS) and Higher-Order Thinking Skills (HOTS). Ultimately, this integration contributes significantly to overcoming learning difficulties in complex and abstract Science topics (e.g., the human digestive system) while also effectively addressing contemporary educational challenges, fostering meaningful learning experiences, and supporting long-term academic success for students.